Religious Moderation Policy in Early Childhood Education Institutions (Current Research in Education: Conference Series Journal, 2024)
This research was motivated by the mainstreaming of religious moderation initiated by the Indonesian government. Religious moderation is currently instructed to be implemented in all educational institutions, one of which is Early Childhood Education (PAUD) institutions. This research method uses a literature study method which involves searching, selecting and analyzing relevant sources. This data was obtained through searching various sources such as articles, journals, books and research reports related to moderation policies in early childhood institutions. The results of this research indicate that religious moderation policies have the potential to create an inclusive and tolerant educational environment. Religious moderation policies in PAUD institutions can provide great benefits in promoting tolerance and better understanding of religious diversity.